2022
DOI: 10.1155/2022/9637831
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Third-Generation Percutaneous Vertebral Augmentation System (PVAS) in Osteoporotic Vertebral Compression Fractures (OVCFs): A Systematic Review and Meta-analysis

Abstract: Purpose. This study aimed to assess whether the third-generation PVAS was superior to percutaneous vertebroplasty (PVP) or percutaneous kyphoplasty (PKP) in treating patients with OVCFs. Methods. Databases, including Pubmed, Embase, and Cochrane library, were searched to identify relevant interventional and observational articles in vivo or in vitro comparing the third-generation PVAS to PVP/PKP in OVCFs patients. A meta-analysis was performed under the guidelines of the Cochrane Reviewer’s Handbook. Results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Third generation kyphoplasty indefinitely restores vertebral height using an expandable scaffold through a mechanical rather than hydraulic opening control prior to injection of the cement. Due to the implantation of a permanent intervertebral scaffold for height maintenance, studies have shown that third generation PK are associated with lower rates of new fractures and a larger postoperative increase in vertebral heights when compared with traditional kyphoplasty [ 5 , 6 ]. Spine Jack® (Stryker Corp, Kalamazoo, MI) specifically may be associated with reduced cement leakage and adjacent vertebral body fractures, along with reduction of the superior endplates allowing for better recovery of the injured disk [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third generation kyphoplasty indefinitely restores vertebral height using an expandable scaffold through a mechanical rather than hydraulic opening control prior to injection of the cement. Due to the implantation of a permanent intervertebral scaffold for height maintenance, studies have shown that third generation PK are associated with lower rates of new fractures and a larger postoperative increase in vertebral heights when compared with traditional kyphoplasty [ 5 , 6 ]. Spine Jack® (Stryker Corp, Kalamazoo, MI) specifically may be associated with reduced cement leakage and adjacent vertebral body fractures, along with reduction of the superior endplates allowing for better recovery of the injured disk [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike minimally invasive injectable cement materials, vertebral implants are primarily composed of implantable metals (Cornelis et al, 2019) (Figure 7). These include the Vertebral Body Stenting (VBS), SpineJack, Kiva, and Osseofix systems, which are based on a similar principle of percutaneous implantation of an expandable vertebral body stent (to restore vertebral height) and the correction of kyphosis; this procedure is referred to as third-generation vertebral body augmentation (Dong et al, 2022).…”
Section: Vertebral Implantsmentioning
confidence: 99%
“…Worldwide, 1.4 million cases of vertebral compression fractures (VCFs) are estimated to occur each year [ 9 ]. Percutaneous vertebroplasty (PVP) has traditionally been performed to treat VCF; however, guidelines from the American Academy of Orthopedic Surgeons strongly recommend against its use, due to its uncertain benefits and known harms [ 17 ]; instead, other surgical treatments are now commonly performed on their own or in combination with cement injection, including percutaneous balloon kyphoplasty (PBKP) and percutaneous vertebral augmentation systems (PVAS) [ 2 , 5 , 8 , 11 ]. These surgical treatments intend to restore and maintain vertebral body height and reduce kyphosis, which in turn decreases low back pain and reduces the risk of mortality [ 2 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have found no clinically relevant differences between PVP, PBKP, and PVAS in their ability to restore vertebral body height and reduce kyphosis, and maintain it in the long-term [ 4 , 7 , 12 , 16 ]. Furthermore, a recent meta-analysis [ 5 ] stated that it is unclear whether PVAS is superior to PBKP or PVP in terms of pain relief and functional improvement. Korovessis et al [ 12 ] compared anterior vertebral body height preoperatively versus at 13–15 months follow-up for PBKP and PVAS, and found an increase of only 23% and 24% respectively, with no significant differences between treatment groups.…”
Section: Introductionmentioning
confidence: 99%